The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s13311-020-00855-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of More Selective Central Nervous System Nrf2-Activating Novel Vinyl Sulfoximine Compounds Compared to Dimethyl Fumarate

Abstract: The Nrf2 transcription factor is a key regulator of redox reactions and considered the main target for the multiple sclerosis (MS) drug dimethyl fumarate (DMF). However, exploration of additional Nrf2-activating compounds is motivated, since DMF displays significant off-target effects and has a relatively poor penetrance to the central nervous system (CNS). We de novo synthesized eight vinyl sulfone and sulfoximine compounds (CH-1–CH-8) and evaluated their capacity to activate the transcription factors Nrf2, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…Moreover, DMF and MMF treatment in animal and primary cultures of CNS cells have been reported to increase the nuclear levels of Nrf2, resulting in increases in the cellular redox potential, GSH and ATP levels, and ΔΨm [ 175 ]. In neurons and astrocytes, DMF and MMF were found to be cytoprotective against OS-induced cellular injury and death, in addition to significantly improving cell viability via upregulation of the Nrf2-dependent antioxidant response, indicated by the intracellular regulation of GSH [ 176 , 177 , 178 ]. Other studies have demonstrated improvements in mitochondrial function following DMF and MMF treatment by upregulating mitochondrial biogenesis in an Nrf2-dependent manner [ 175 ].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Moreover, DMF and MMF treatment in animal and primary cultures of CNS cells have been reported to increase the nuclear levels of Nrf2, resulting in increases in the cellular redox potential, GSH and ATP levels, and ΔΨm [ 175 ]. In neurons and astrocytes, DMF and MMF were found to be cytoprotective against OS-induced cellular injury and death, in addition to significantly improving cell viability via upregulation of the Nrf2-dependent antioxidant response, indicated by the intracellular regulation of GSH [ 176 , 177 , 178 ]. Other studies have demonstrated improvements in mitochondrial function following DMF and MMF treatment by upregulating mitochondrial biogenesis in an Nrf2-dependent manner [ 175 ].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…The transcription factor Nrf2 has been identified as the main therapeutic target of DMF in several cell types 42 , 46 48 . Electrophilic agents such as DMF and its active metabolites (e.g monomethyl fumarate (MMF)) facilitates Nrf2 activation via Keap1 49 , 50 .…”
Section: Resultsmentioning
confidence: 99%
“…[63] However, the only case study reported so far is a recent series of vinyl sulfoximines which activate the transcription factor Nrf2. [64] While Nrf2 is considered the main target of the multiple sclerosis drug dimethyl fumarate (43, Figure 18), exploration of additional Nrf2-activating compounds is motivated by its significant off-target effects and low CNS penetration. Against this backdrop, vinyl sulfones like VSC2 (44, Figure 18) were recently shown to increase Nrf2 levels via covalent interaction with certain cysteines in Keap1, leading to Nrf2 activation.…”
Section: Covalent Inhibitionmentioning
confidence: 99%
“…[65] Carlström and co-workers have evaluated a series of VSC2 sulfoximine analogues employing a broad variety of substituents at the sulfoximine nitrogen. [64] The N-methyl analogue CH-3 (45, Figure 18) and dimethyl fumarate displayed comparable activation of Nrf2 in vitro, but N-methyl sulfoximine 45 revealed less off-target effects in vitro and in vivo. Unfortunately, the publication does not provide any insights into the mode of action of vinyl sulfoximine CH-3, but studies with structurally related chalcones and vinyl sulfones suggest that the compound is acting as a covalent inhibitor.…”
Section: Covalent Inhibitionmentioning
confidence: 99%